Revisiting the Economics and Terrorism Nexus: collective Deprivation, Ideology and Domestic Radicalization in the US (1948–2016) - Varaine, Simon (Journal of quantitative criminology, 2020)
Studies generally find no relationship between economic deprivation and terrorist activities, leading to the conclusion that economic conditions have no role in the emergence of terrorist movements. The present paper challenges this conclusion. It argues that collective deprivation affects participation into terrorism, but in different directions depending on the ideology of terrorist movements: far-right terrorism should mobilize more under times of collective deprivation while far-left terrorism should mobilize more under times of collective improvement.